Internet addiction and its association with life satisfaction among university students in Bangladesh - Mondal, Md. Abdul Hannan; Khatun, Tahmina; Haque, Moynul; Mondal, Md. Nazrul Islam; Hossain, Md. Golam (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Internet addiction (IA) is a serious issue for students because it hampers their daily activities and academic performance negatively impacting mental health. Therefore, this study aimed to determine the prevalence of IA and the factors associated with it among university students. Methods: A total of 1,168 students of four Bangladeshi universities (50.2% males, 49.8% females, mean age 22.7 and standard deviation 2.2 years) were collected using multistage cluster sampling for this cross-sectional study. The Bangla-adapted Young’s Internet Addiction Test (IAT) was used to assess the presence of IA. Results: A total of 78% of individuals had IA. The key factors associated with IA were marital status, self-reported physical health condition, sleep quality, physical exercise, social engagement, and life satisfaction. Students who reported dissatisfaction with life were more likely to have IA than those who were satisfied (92.8% versus 69.8%). Unmarried individuals were more likely to experience IA compared to married individuals (83.9% versus 63.2%). Respondents with poor physical health status exhibited higher IA rates than those with good physical health status (91.5% versus 62.1%). Higher IA was found to be more prevalent among individuals with poor sleep quality than those with good sleep (89.2% versus 59.8%). Individuals who did not engage in social activities were more likely to have IA than those who engaged in social activities (81.6% versus 71.8%). Multiple logistic regression analysis supported these relationships. Conclusion: IA is widely prevalent among university students, with nearly three-fourths of them being addicted. Therefore, university administrators and relevant authorities should take necessary measures to mitigate the adverse effects of IA.